The Utilization of Gamification and Game-Based Learning in the Independent Curriculum: Systematic Literature Review on Student Motivation and Learning Outcomes - Dudun Ubaedullah; Nasirudin; Sita Husnul Khotimah; Muhammad Mamduh Nuruddin (Edukasiana: Journal of Islamic Education, 2026)
The implementation of the Merdeka Curriculum requires adaptive, student-centered learning approaches that enhance meaningful engagement. Gamification and Game-Based Learning (GBL) have emerged as innovative strategies to address this challenge. This study aims to analyze the use of gamification and GBL within the Merdeka Curriculum and their impact on students' motivation and learning outcomes. A Systematic Literature Review (SLR) was conducted using the PRISMA 2020 protocol, searching the Scopus, ScienceDirect, ERIC, and SINTA databases for publications from 2019 to 2025. Of 842 identified articles, 32 met the inclusion criteria and were thematically analyzed. The findings reveal that gamification and GBL consistently improve intrinsic motivation, cognitive engagement, and both cognitive and affective learning outcomes across educational levels. Platforms such as Kahoot!, Quizizz, Minecraft Education, and Wordwall are the most frequently used. However, challenges persist regarding teacher readiness, digital infrastructure, and alignment with the Pancasila Student Profile. The study concludes that integrating gamification and GBL significantly contributes to achieving the goals of the Merdeka Curriculum.